Lightweight gypsum leveling putty powder with thermal insulation effect
By using amino acidified chitosan and crosslinked coating products as insulation fillers in putty powder, the problems of low strength and construction difficulties in existing building insulation materials are solved, and efficient thermal insulation effect and good bonding performance are achieved.
Patent Information
- Application Number
- CN202510183139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing building insulation materials have problems such as low strength, poor flame retardancy and difficulty in construction and maintenance. It is urgent to develop new insulation materials to improve building energy-saving performance.
A light gypsum leveling putty powder including desulfurized gypsum powder, insulation filler, ash calcium powder, silicate cement, hydroxypropyl methyl cellulose and redispersible latex powder is used to form amino acidified chitosan by reaction between chitosan and glycine, and cross-linking and coating treatment is used to form a cross-linking complex of cuprous oxide and amino acidified chitosan as the core, covering the coating product of the titanium dioxide layer, doping it into SiO2 aerogel to form an insulation filler.
The putty powder has good bonding strength and low thermal conductivity, which significantly improves the insulation effect and service performance, and is not easy to fall off.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wall thermal insulation coatings, in particular to a lightweight gypsum leveling putty powder with thermal insulation effect. Background Art
[0002] Putty powder for interior and exterior walls of buildings is a functional material that matches architectural coatings. Its main function is to level the wall, improve the decorative effect of coatings, and reduce the amount of wall coatings per unit area. The thermal insulation materials of modern buildings are mainly expanded polystyrene foam boards, extruded polystyrene foam boards, polyurethane and phenolic resin foam materials. Although these thermal insulation materials have good thermal insulation and waterproof properties, they also have disadvantages such as low strength, poor flame retardancy, and difficulty in construction and maintenance. Therefore, it is urgent to study new thermal insulation materials to solve these problems, and building thermal insulation materials have also become a hot spot in my country's building energy conservation field. Putty powder with thermal insulation effect is widely used in the decoration of building thermal insulation walls as a high-solid powder coating. In the next few years, water-resistant putty will occupy more market. Summary of the invention
[0003] To this end, the present invention provides a lightweight gypsum leveling putty powder with thermal insulation effect, comprising desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder; wherein the preparation method of the thermal insulation filler is:
[0004] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to an MES buffer solution, stirring and mixing for more than 100 minutes, and then adding the mixture to the chitosan solution kept at a constant temperature of 35±3° C. in a water bath, and continuing to keep the temperature at 35±3° C. and stirring for more than 48 hours after the addition is completed, to obtain an amino acid-containing chitosan solution;
[0005] (2) preparing a mixed aqueous solution of copper sulfate and glucose; heating the amino acid-containing chitosan solution to 55±3° C. in a water bath and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and stirring at 55±3° C. for more than 5 hours after the addition is completed, and then adding sodium hydroxide solution to adjust the pH of the solution to 10-11, and then continue to stir at 55±3° C. for more than 30 minutes, and then adding epichlorohydrin under stirring, and continue to stir at 55±3° C. for more than 3 hours after the addition, and finally separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying to obtain a cross-linked product;
[0006] (3) adding the cross-linked product to anhydrous ethanol and stirring for more than 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3° C. in a water bath and keeping it warm, then adding ammonia water to the alcohol suspension under stirring, and continuing to stir at a constant temperature of 45±3° C. for more than 30 minutes after adding, then adding tetrabutyl titanate under stirring, and stirring at a constant temperature of 45±3° C. for more than 20 hours after adding, then separating the solid and the liquid, washing the solid phase with ethanol for more than 2 times, and then washing with deionized water for more than 3 times, and drying to obtain a coated product;
[0007] (4) Hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water are mixed to form an active agent solution; the active agent solution is stirred, and then the coated product and methyltrimethoxysilane are added under stirring, and the solution is stirred for more than 30 minutes after the addition is completed, and then ammonia water is added, and the solution is stirred for another 3-4 minutes after the addition to obtain a sol, and the sol is poured into a constant temperature mold at 60±3°C and aged for more than 36 hours, and then solvent replacement purification is performed with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
[0008] Furthermore, the components are calculated by weight as follows: 100 parts of desulfurized gypsum powder; 15-20 parts of thermal insulation filler; 8-12 parts of lime powder; 5-10 parts of silicate cement; 4-6 parts of hydroxypropyl methylcellulose; and 0.8-1.2 parts of redispersible latex powder.
[0009] Furthermore, in the step (1), the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 0.8-1.2 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine: N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 2-4 g: 16-18 g: 7-9 g: 200 mL; and the mixed solution is added to the chitosan solution in a volume ratio of mixed solution: chitosan solution = 1:2.
[0010] Furthermore, the solubility of the MES buffer is 0.5 M, and the pH is 6.
[0011] Furthermore, in the step (2), in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 6-8 g / 100 mL, the concentration of glucose is 4-5 g / 100 mL, and the solvent is water; the volume ratio of the mixed aqueous solution of copper sulfate and glucose and epichlorohydrin added to the amino acid-containing chitosan solution is amino acid-containing chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 8-11:7-8:1.
[0012] Furthermore, the concentration of the solute in the sodium hydroxide solution is 0.5 mol / L, and the solvent is water.
[0013] Furthermore, in the step (3), the cross-linked product is added to anhydrous ethanol in a mass ratio of cross-linked product: anhydrous ethanol = 1:100; ammonia water and tetrabutyl titanate are added to the alcohol suspension in a volume ratio of alcohol suspension: ammonia water: tetrabutyl titanate = 100:10-15:4-6; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water.
[0014] Furthermore, in the step (4), the mixing ratio of the hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 1-3 g: 0.1-0.2 mL: 60 mL; the ratio of the coated product, methyltrimethoxysilane and ammonia water added to the active agent solution is active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50 mL: 2-3 g: 18-20 mL: 2-4 mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water.
[0015] The beneficial effect of the present invention is that the putty powder prepared by the method of the present invention has good bonding strength and low thermal conductivity, indicating that the putty powder has good thermal insulation effect and is not easy to fall off, which greatly improves the use performance of the putty powder. This is mainly due to the fact that the present invention firstly grafts glycine onto chitosan through the action of chitosan and glycine to form amino acid-containing chitosan, increases the number of surface active functional groups of the filler itself, is conducive to improving the binding force between the filler and other components of the putty powder, and improves the strength of the putty powder; at the same time, the surface active functional groups are increased to improve the chelation of chitosan to metal ions, which is conducive to the subsequent cross-linking of cuprous oxide particles and coating of titanium oxide, so that the cross-linking rate and coating rate are higher. Secondly, by adding copper sulfate and glucose, using liquid phase precipitation and reduction reaction, cuprous oxide and chitosan-based molecules are cross-linked to form a cross-linked complex, and then titanium dioxide is coated on the cross-linked complex to form a coated product with a cross-linked complex of cuprous oxide and amino acid-containing chitosan as the core and a titanium dioxide layer coated. The coated product is doped into SiO2 aerogel to finally form the thermal insulation filler of the present invention. On the one hand, the thermal insulation filler utilizes the special structure of aerogel to achieve good thermal insulation effects, and on the other hand, utilizes the high reflectivity of cuprous oxide to thermal radiation to reduce the absorption of heat by the putty powder coating, thereby improving the thermal insulation effects; utilizing the characteristics of the titanium dioxide coating layer with a high refractive index, stable chemical properties, and low toxicity, the reflectivity of the filler to heat is increased, the stability of the filler is improved, and the thermal insulation effect is further optimized. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments.
[0017] Example 1
[0018] A lightweight gypsum leveling putty powder with thermal insulation effect, comprising desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); each component is calculated by weight as follows: 100 parts of desulfurized gypsum powder; 15 parts of thermal insulation filler; 8 parts of lime powder; 5 parts of silicate cement; 4 parts of hydroxypropyl methylcellulose; and 0.8 parts of redispersible latex powder. The preparation method of the thermal insulation filler is as follows:
[0019] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 0.8 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine to 1:1. : N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 2g: 16g: 7g: 200mL; the solubility of the MES buffer is 0.5M, pH = 6; stirring and mixing for 100min, then adding the mixed solution to the chitosan solution kept at a constant temperature of 35±3°C in a water bath, and the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3°C and stir for 48h to obtain an amino acid-containing chitosan solution;
[0020] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 6 g / 100 mL, the concentration of glucose is 4 g / 100 mL, and the solvent is water; heating the amino acid-containing chitosan solution in a water bath to 55±3° C., then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and after the addition is completed, stirring at 55±3° C. for 5 h, and then adding sodium hydroxide solution to adjust the pH of the solution to 10, and dissolving the sodium hydroxide solution in the chitosan solution; The concentration of the substance is 0.5 mol / L, and the solvent is water; continue to keep warm and stir at 55±3°C for 30 minutes, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution in a volume ratio of amino acid-containing chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 8:7:1; continue to keep warm and stir at 55±3°C for 3 hours after adding the materials, finally separate the solid and liquid, wash the solid phase with deionized water until the washed liquid is neutral, and dry at 60°C for 5 hours to obtain a cross-linked product;
[0021] (3) adding the cross-linked product to anhydrous ethanol, wherein the mass ratio of the cross-linked product to the anhydrous ethanol is cross-linked product: anhydrous ethanol = 1:100; stirring for 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3°C in a water bath for insulation, then adding ammonia water to the alcohol suspension under stirring, continuing to stir at a constant temperature of 45±3°C for 30 minutes after adding, and then adding tetrabutyl titanate under stirring, wherein the volume ratio of ammonia water and tetrabutyl titanate to the alcohol suspension is alcohol suspension: ammonia water: tetrabutyl titanate = 100:10:4; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water; stirring at a constant temperature of 45±3°C for 20 hours after adding, then separating the solid and the liquid, washing the solid phase with ethanol twice, and then washing with deionized water three times, and drying at 60°C for 5 hours to obtain a coated product;
[0022] (4) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 1 g: 0.1 mL: 60 mL; stirring the active agent solution, and then adding the coated product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the coated product, methyltrimethoxysilane and ammonia water to the active agent solution. The amount ratio is active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50mL: 2g: 18mL: 2mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring is continued for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement purification is carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, drying for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
[0023] Example 2
[0024] A lightweight gypsum leveling putty powder with thermal insulation effect, comprising desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); each component is calculated by weight as follows: 100 parts of desulfurized gypsum powder; 16 parts of thermal insulation filler; 10 parts of lime powder; 7 parts of silicate cement; 5 parts of hydroxypropyl methylcellulose; 1 part of redispersible latex powder. The preparation method of the thermal insulation filler is:
[0025] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 1 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine: N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 3g: 17g: 8g: 200mL; the solubility of the MES buffer is 0.5M, pH = 6; stirring and mixing for 100min, then adding the mixed solution to the chitosan solution kept at a constant temperature of 35±3°C in a water bath, and the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3°C and stir for 48h to obtain an amino acid-containing chitosan solution;
[0026] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 7 g / 100 mL, the concentration of glucose is 4 g / 100 mL, and the solvent is water; heating the amino acid-containing chitosan solution in a water bath to 55±3° C., and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and after the addition is completed, stirring at 55±3° C. for 5 h, and then adding sodium hydroxide solution to adjust the pH of the solution to 10, and dissolving the sodium hydroxide solution in the chitosan solution; The concentration of the substance is 0.5 mol / L, and the solvent is water; continue to keep warm and stir at 55±3°C for 30 minutes, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution in a volume ratio of amino acid-containing chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 9:7:1; continue to keep warm and stir at 55±3°C for 3 hours after adding the materials, finally separate the solid and liquid, wash the solid phase with deionized water until the washed liquid is neutral, and dry at 60°C for 5 hours to obtain a cross-linked product;
[0027] (3) adding the cross-linked product to anhydrous ethanol, wherein the mass ratio of the cross-linked product to the anhydrous ethanol is cross-linked product: anhydrous ethanol = 1:100; stirring for 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3°C in a water bath for insulation, then adding ammonia water to the alcohol suspension under stirring, continuing to stir at a constant temperature of 45±3°C for 30 minutes after adding, and then adding tetrabutyl titanate under stirring, wherein the volume ratio of ammonia water and tetrabutyl titanate to the alcohol suspension is alcohol suspension: ammonia water: tetrabutyl titanate = 100:12:5; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water; stirring at a constant temperature of 45±3°C for 20 hours after adding, then separating the solid and the liquid, washing the solid phase with ethanol twice, and then washing with deionized water three times, and drying at 60°C for 5 hours to obtain a coated product;
[0028] (4) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 2g: 0.1mL: 60mL; stirring the active agent solution, and then adding the coated product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the coated product, methyltrimethoxysilane and ammonia water to the active agent solution. The amount ratio is active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50mL: 2g: 19mL: 3mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring is continued for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement purification is carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, drying for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
[0029] Example 3
[0030] A lightweight gypsum leveling putty powder with thermal insulation effect, comprising desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); each component is calculated by weight as follows: 100 parts of desulfurized gypsum powder; 18 parts of thermal insulation filler; 10 parts of lime powder; 8 parts of silicate cement; 5 parts of hydroxypropyl methylcellulose; 1 part of redispersible latex powder. The preparation method of the thermal insulation filler is:
[0031] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 1 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine: N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 3g: 17g: 8g: 200mL; the solubility of the MES buffer is 0.5M, pH = 6; stirring and mixing for 100min, then adding the mixed solution to the chitosan solution kept at a constant temperature of 35±3°C in a water bath, and the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3°C and stir for 48h to obtain an amino acid-containing chitosan solution;
[0032] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 7 g / 100 mL, the concentration of glucose is 5 g / 100 mL, and the solvent is water; heating the amino acid-containing chitosan solution in a water bath to 55±3° C., and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and after the addition is completed, stirring is maintained at 55±3° C. for 5 hours, and then sodium hydroxide solution is added to adjust the pH of the solution to 10, and the solute in the sodium hydroxide solution is The concentration is 0.5 mol / L, and the solvent is water; continue to stir at 55±3°C for 30 min, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the amino acid chitosan solution in a volume ratio of amino acid chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 10:8:1; continue to stir at 55±3°C for 3 h after adding, finally separate the solid and liquid, wash the solid phase with deionized water until the liquid after washing is neutral, and dry at 60°C for 5 h to obtain a cross-linked product;
[0033] (3) adding the cross-linked product to anhydrous ethanol, wherein the mass ratio of the cross-linked product to the anhydrous ethanol is cross-linked product: anhydrous ethanol = 1:100; stirring for 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3°C in a water bath for insulation, then adding ammonia water to the alcohol suspension under stirring, and continuing to stir at a constant temperature of 45±3°C for 30 minutes after adding, and then adding tetrabutyl titanate under stirring, and adding ammonia water and tetrabutyl titanate to the alcohol suspension in a volume ratio of alcohol suspension: ammonia water: tetrabutyl titanate = 100:14:5; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water; stirring at a constant temperature of 45±3°C for 20 hours after adding, and then separating the solid and liquid, washing the solid phase with ethanol twice, and then washing with deionized water three times, and drying at 60°C for 5 hours to obtain a coated product;
[0034] (4) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 2g: 0.2mL: 60mL; stirring the active agent solution, and then adding the coated product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the coated product, methyltrimethoxysilane and ammonia water to the active agent solution. The amount ratio is active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50mL: 3g: 19mL: 3mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring is continued for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement purification is carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, drying for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
[0035] Example 4
[0036] A lightweight gypsum leveling putty powder with thermal insulation effect, comprising desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); each component is calculated by weight as follows: 100 parts of desulfurized gypsum powder; 20 parts of thermal insulation filler; 12 parts of lime powder; 10 parts of silicate cement; 6 parts of hydroxypropyl methylcellulose; and 1.2 parts of redispersible latex powder. The preparation method of the thermal insulation filler is as follows:
[0037] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the amount ratio of chitosan added to the acetic acid solution is chitosan: acetic acid solution = 1.2 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the amount ratio of glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to the MES buffer is glycine. : N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 4g: 18g: 9g: 200mL; the solubility of the MES buffer is 0.5M, pH = 6; stirring and mixing for 100min, then adding the mixed solution to the chitosan solution kept at 35±3°C in a water bath, the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3°C and stir for 48h to obtain an amino acid-containing chitosan solution;
[0038] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 8 g / 100 mL, the concentration of glucose is 5 g / 100 mL, and the solvent is water; heating the amino acid-containing chitosan solution in a water bath to 55±3° C., and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and after the addition is completed, stirring is maintained at 55±3° C. for 5 hours, and then sodium hydroxide solution is added to adjust the pH of the solution to 10, and the solute in the sodium hydroxide solution is The concentration is 0.5 mol / L, and the solvent is water; continue to stir at 55±3°C for 30 min, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the amino acid chitosan solution in a volume ratio of amino acid chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 11:8:1; continue to stir at 55±3°C for 3 h after adding, finally separate the solid and liquid, wash the solid phase with deionized water until the liquid after washing is neutral, and dry at 60°C for 5 h to obtain a cross-linked product;
[0039] (3) adding the cross-linked product to anhydrous ethanol, wherein the mass ratio of the cross-linked product to the anhydrous ethanol is cross-linked product: anhydrous ethanol = 1:100; stirring for 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3°C in a water bath for insulation, then adding ammonia water to the alcohol suspension under stirring, continuing to stir at a constant temperature of 45±3°C for 30 minutes after adding, and then adding tetrabutyl titanate under stirring, wherein the volume ratio of ammonia water and tetrabutyl titanate to the alcohol suspension is alcohol suspension: ammonia water: tetrabutyl titanate = 100:15:6; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water; stirring at a constant temperature of 45±3°C for 20 hours after adding, then separating the solid and the liquid, washing the solid phase with ethanol twice, and then washing with deionized water three times, and drying at 60°C for 5 hours to obtain a coated product;
[0040] (4) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 3g: 0.2mL: 60mL; stirring the active agent solution, and then adding the coated product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the coated product, methyltrimethoxysilane and ammonia water to the active agent solution. The amount ratio is active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50mL: 3g: 20mL: 4mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring is continued for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement purification is carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, drying for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
[0041] Comparative Example 1
[0042] A putty powder for comparison includes desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); the components are calculated by weight as follows: 100 parts of desulfurized gypsum powder; 18 parts of thermal insulation filler; 10 parts of lime powder; 8 parts of silicate cement; 5 parts of hydroxypropyl methylcellulose; 1 part of redispersible latex powder. The preparation method of the thermal insulation filler is:
[0043] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 1 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of N-hydroxysuccinimide: Imidide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 17 g: 8 g: 200 mL; the solubility of the MES buffer is 0.5 M, pH = 6; stirring and mixing for 100 min, then adding the mixed solution to the chitosan solution kept at 35±3° C. in a water bath, the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3° C. and stir for 48 h to obtain the pretreated chitosan solution of this comparative example;
[0044] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 7 g / 100 mL, the concentration of glucose is 5 g / 100 mL, and the solvent is water; heating the pretreated chitosan solution in a water bath to 55±3° C., and then adding the mixed aqueous solution of copper sulfate and glucose to the pretreated chitosan solution under stirring, and after the addition is completed, stirring is maintained at 55±3° C. for 5 h, and then sodium hydroxide solution is added to adjust the pH of the solution to 10, and the solute in the sodium hydroxide solution is The concentration is 0.5 mol / L, and the solvent is water; continue to stir at 55±3°C for 30 minutes, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the pretreated chitosan solution in a volume ratio of pretreated chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 10:8:1; continue to stir at 55±3°C for 3 hours after adding, finally separate the solid and liquid, wash the solid phase with deionized water until the washed liquid is neutral, and dry at 60°C for 5 hours to obtain a cross-linked product;
[0045] (3) adding the cross-linked product to anhydrous ethanol, wherein the mass ratio of the cross-linked product to the anhydrous ethanol is cross-linked product: anhydrous ethanol = 1:100; stirring for 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3°C in a water bath for insulation, then adding ammonia water to the alcohol suspension under stirring, and continuing to stir at a constant temperature of 45±3°C for 30 minutes after adding, and then adding tetrabutyl titanate under stirring, and adding ammonia water and tetrabutyl titanate to the alcohol suspension in a volume ratio of alcohol suspension: ammonia water: tetrabutyl titanate = 100:14:5; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water; stirring at a constant temperature of 45±3°C for 20 hours after adding, and then separating the solid and liquid, washing the solid phase with ethanol twice, and then washing with deionized water three times, and drying at 60°C for 5 hours to obtain a coated product;
[0046] (4) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 2 g: 0.2 mL: 60 mL; stirring the active agent solution, and then adding the coated product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the coated product, methyltrimethoxysilane, and ammonia water to the active agent solution in a ratio of The active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50mL: 3g: 19mL: 3mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement and purification are carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, dried for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler described in this comparative example.
[0047] Comparative Example 2
[0048] A putty powder for comparison includes desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder (Wacker Chemical latex powder 4115N); the components are calculated by weight as follows: 100 parts of desulfurized gypsum powder; 18 parts of thermal insulation filler; 10 parts of lime powder; 8 parts of silicate cement; 5 parts of hydroxypropyl methylcellulose; 1 part of redispersible latex powder. The preparation method of the thermal insulation filler is:
[0049] (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 1 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to an MES buffer, wherein the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine: N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 3g: 17g: 8g: 200mL; the solubility of the MES buffer is 0.5M, pH = 6; stirring and mixing for 100min, then adding the mixed solution to the chitosan solution kept at a constant temperature of 35±3°C in a water bath, and the volume ratio of the mixed solution to the chitosan solution is mixed solution: chitosan solution = 1:2; after the addition is completed, continue to keep warm at 35±3°C and stir for 48h to obtain an amino acid-containing chitosan solution;
[0050] (2) preparing a mixed aqueous solution of copper sulfate and glucose; in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 7 g / 100 mL, the concentration of glucose is 5 g / 100 mL, and the solvent is water; heating the amino acid-containing chitosan solution in a water bath to 55±3° C., and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and after the addition is completed, stirring is maintained at 55±3° C. for 5 hours, and then sodium hydroxide solution is added to adjust the pH of the solution to 10, and the solute in the sodium hydroxide solution is The concentration is 0.5 mol / L, and the solvent is water; continue to stir at 55±3°C for 30 min, then add epichlorohydrin under stirring, add the mixed aqueous solution of copper sulfate and glucose to the amino acid chitosan solution in a volume ratio of amino acid chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 10:8:1; continue to stir at 55±3°C for 3 h after adding, finally separate the solid and liquid, wash the solid phase with deionized water until the liquid after washing is neutral, and dry at 60°C for 5 h to obtain a cross-linked product;
[0051] (3) mixing hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water to form an active agent solution; the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 2 g: 0.2 mL: 60 mL; stirring the active agent solution, and then adding the cross-linked product and methyltrimethoxysilane under stirring, and continuing to stir the solution for 30 minutes after the addition is completed, and then adding ammonia water, and adding the cross-linked product, methyltrimethoxysilane, and ammonia water to the active agent solution in a ratio of The active agent solution: cross-linked product: methyltrimethoxysilane: ammonia water = 50mL: 3g: 19mL: 3mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water; after adding the materials, stirring for 3 minutes to obtain a sol, the sol is poured into a constant temperature mold at 60±3°C and aged for 36 hours, and then solvent replacement and purification are carried out with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment (12MPa, 50°C, drying for 12 hours) to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler described in this comparative example.
[0052] Example 5
[0053] Weigh each putty powder raw material according to the weight of each embodiment and comparative example, mix each raw material evenly, add water to the mixed raw material, adjust to a putty powder slurry with a moisture content of 40wt%, apply the putty powder slurry to a putty powder coating according to the requirements of standard JG / T298-2010, and cure the coating at 23±2℃ and 50±5% humidity for 7 days, and then test the performance. The bonding strength of the putty powder prepared by the method described in the above embodiments and comparative examples is tested according to the requirements of standard JG / T298-2010; the thermal conductivity of the putty powder prepared by the method described in the above embodiments and comparative examples is tested according to the requirements of standard GB / T 10295-2008; the results are shown in Table 1.
[0054] As can be seen from Table 1, the putty powder prepared by the method of the present invention has good bonding strength and low thermal conductivity, indicating that the putty powder has good thermal insulation effect and is not easy to fall off, which greatly improves the use performance of the putty powder. By comparing Example 3 of the present invention and the comparative examples, it can be seen that the present invention can significantly improve the thermal insulation and bonding properties of the putty powder by adding aerogel particles as thermal insulation filler to the putty powder and crosslinking, coating and other treatments of the aerogel. This is mainly due to: the present invention firstly grafts glycine onto chitosan through the action of chitosan and glycine to form amino acid-containing chitosan, which increases the number of surface active functional groups of the filler itself, which is beneficial to improve the bonding force between the filler and other components of the putty powder and improve the strength of the putty powder; at the same time, the surface active functional groups are increased to improve the chelation of chitosan to metal ions, which is beneficial to the subsequent crosslinking of cuprous oxide particles and coating of titanium oxide, so that the crosslinking rate and coating rate are higher. Secondly, by adding copper sulfate and glucose, using liquid phase precipitation and reduction reaction, cuprous oxide and chitosan-based molecules are cross-linked to form a cross-linked complex, and then titanium dioxide is coated on the cross-linked complex to form a coated product with a cross-linked complex of cuprous oxide and amino acid chitosan as the core and a titanium dioxide layer. The coated product is doped into SiO2 aerogel to finally form the thermal insulation filler described in the present invention. On the one hand, the thermal insulation filler utilizes the special structure of the aerogel to achieve good thermal insulation effects, and on the other hand, utilizes the high reflectivity of cuprous oxide to thermal radiation to reduce the absorption of heat by the putty powder coating, thereby improving the thermal insulation effect; utilizing the characteristics of the titanium dioxide coating layer with a high refractive index, stable chemical properties, and low toxicity, the reflectivity of the filler to heat is improved, the stability of the filler is improved, and the thermal insulation effect is further optimized.
[0055] Table 1
[0056] Experimental Group Bond strength (MPa) Thermal conductivity (W / m·k) Example 1 0.71 0.03 Example 2 0.76 0.02 Example 3 0.80 0.02 Example 4 0.78 0.02 Comparative Example 1 0.63 0.05 Comparative Example 2 0.74 0.06
[0057] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A lightweight gypsum leveling putty powder with thermal insulation effect, characterized in that: The invention comprises desulfurized gypsum powder, thermal insulation filler, lime powder, silicate cement, hydroxypropyl methylcellulose and redispersible latex powder; wherein the preparation method of the thermal insulation filler is as follows: (1) adding chitosan to an acetic acid solution, stirring and dissolving to obtain a chitosan solution; adding glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to an MES buffer solution, stirring and mixing for more than 100 minutes, and then adding the mixture to the chitosan solution kept at a constant temperature of 35±3° C. in a water bath, and continuing to keep the temperature at 35±3° C. and stirring for more than 48 hours after the addition is completed, to obtain an amino acid-containing chitosan solution; (2) preparing a mixed aqueous solution of copper sulfate and glucose; heating the amino acid-containing chitosan solution to 55±3° C. in a water bath and then adding the mixed aqueous solution of copper sulfate and glucose to the amino acid-containing chitosan solution under stirring, and stirring at 55±3° C. for more than 5 hours after the addition is completed, and then adding sodium hydroxide solution to adjust the pH of the solution to 10-11, and then continue to stir at 55±3° C. for more than 30 minutes, and then adding epichlorohydrin under stirring, and continue to stir at 55±3° C. for more than 3 hours after the addition, and finally separating the solid and liquid, washing the solid phase with deionized water until the washed liquid is neutral, and drying to obtain a cross-linked product; (3) adding the cross-linked product to anhydrous ethanol and stirring for more than 30 minutes to obtain an alcohol suspension; heating the alcohol suspension to 45±3° C. in a water bath and keeping it warm, then adding ammonia water to the alcohol suspension under stirring, and continuing to stir at a constant temperature of 45±3° C. for more than 30 minutes after adding, then adding tetrabutyl titanate under stirring, and stirring at a constant temperature of 45±3° C. for more than 20 hours after adding, then separating the solid and the liquid, washing the solid phase with ethanol for more than 2 times, and then washing with deionized water for more than 3 times, and drying to obtain a coated product; (4) Hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water are mixed to form an active agent solution; the active agent solution is stirred, and then the coated product and methyltrimethoxysilane are added under stirring, and the solution is stirred for more than 30 minutes after the addition is completed, and then ammonia water is added, and the solution is stirred for another 3-4 minutes after the addition to obtain a sol, and the sol is poured into a constant temperature mold at 60±3°C and aged for more than 36 hours, and then solvent replacement purification is performed with deionized water and ethanol in succession, and after purification, it is dried under a CO2 supercritical environment to obtain an aerogel, and the aerogel is crushed to obtain the thermal insulation filler.
2. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: The components are calculated by weight as follows: 100 parts of desulfurized gypsum powder; 15-20 parts of thermal insulation filler; 8-12 parts of lime powder; 5-10 parts of silicate cement; 4-6 parts of hydroxypropyl methylcellulose; and 0.8-1.2 parts of redispersible latex powder.
3. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: In the step (1), the chitosan is added to the acetic acid solution in a ratio of chitosan: acetic acid solution = 0.8-1.2 g: 100 mL, wherein the mass percentage of the solute in the acetic acid is 1%, and the solvent is water; the glycine, N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the MES buffer in a ratio of glycine: N-hydroxysuccinimide: 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride: MES buffer = 2-4 g: 16-18 g: 7-9 g: 200 mL; and the mixed solution is added to the chitosan solution in a volume ratio of mixed solution: chitosan solution = 1:
2.
4. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: The solubility of the MES buffer is 0.5 M, and the pH is 6.
5. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: In the step (2), in the mixed aqueous solution of copper sulfate and glucose, the concentration of copper sulfate is 6-8 g / 100 mL, the concentration of glucose is 4-5 g / 100 mL, and the solvent is water; the volume ratio of the mixed aqueous solution of copper sulfate and glucose and epichlorohydrin added to the amino acid-containing chitosan solution is amino acid-containing chitosan solution: mixed aqueous solution of copper sulfate and glucose: epichlorohydrin = 8-11:7-8:
1.
6. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: The concentration of the solute in the sodium hydroxide solution is 0.5 mol / L, and the solvent is water.
7. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: In the step (3), the cross-linked product is added to anhydrous ethanol in a mass ratio of the cross-linked product: Anhydrous ethanol = 1:100; ammonia water and tetrabutyl titanate are added to the alcohol suspension in a volume ratio of alcohol suspension: ammonia water: tetrabutyl titanate = 100:10-15:4-6; wherein the mass percentage of the solute in the ammonia water is 5%, and the solvent is water.
8. The lightweight gypsum leveling putty powder with thermal insulation effect according to claim 1, characterized in that: In the step (4), the mixing ratio of hexadecyltrimethylammonium bromide, glacial acetic acid and deionized water is hexadecyltrimethylammonium bromide: glacial acetic acid: deionized water = 1-3 g: 0.1-0.2 mL: 60 mL; the coated product, methyltrimethoxysilane and ammonia water are added to the active agent solution in the ratio of active agent solution: coated product: methyltrimethoxysilane: ammonia water = 50 mL: 2-3 g: 18-20 mL: 2-4 mL, wherein the mass percentage of the solute in the ammonia water is 3%, and the solvent is water.